HYDROTREATMENT KATALITIK MINYAK RINGAN DENGAN KATALIS NIMO DAN PENGARUH SPESIES NITROGEN - Murti, Sri Djangkung Sumbogo; Hartiniati, Hartiniati; Eliyanti, Agustina (Badan Pengkajian dan Penerapan Teknologi, 2010)
Gas Oil fraction of petroleum was hydrotreated (hydrodesulfurization, HDS) overNiMo/Al2O3 catalyst in a 100 ml autoclave reactor. The reaction was conducted at340 oC under 5MPa H2 pressure for 60 min. to investigate the correlation ofnitrogen species in the HDS. The inhibition effects of these species are alsoinvestigated by using original and its N-free gas oil. Hydrogen renewal betweenstages was attempted to reveal an additional effect of the by-products such asH2S. All species in the gas oils were analyzed by GC-AED before and afterhydrotreatment. HDS over NiMo/Al2O3 was largely improved by removal ofnitrogen species. Refractory sulfur species were effectively removed by theremoval of nitrogen species and renewal of hydrogen in staged HDS, showingsynergy effects due to simultaneous removal of two inhibitors.Kata kunci: gas oil, hydrodesulfurization, nitrogen inhibition, GC-AED